WANPRESTASI DAN PENYELESAIANNYA DALAM PERJANJIAN SEWA-MENYEWA MOBIL : STUDI KASUS DI CV ILHAM MOTOR JALAN DAHLIA GANDU MLARAK PONOROGO TAHUN 2021) - Layla (Muara Aksara: Jurnal Ilmiah Multidisipliner, 2025)
Default and Settlement in Car Rental Agreements (Case Study on CV Ilham Motor Dahlia Jalan Gandu Mlarak Ponorogo) in 2021. The formulation of the problem in this research is (1) How does a default occur in a car rental agreement at CV Ilham Motor Jalan Dahlia Gandu Mlarak Ponorogo? , (2) What are the forms of default that arise in the implementation of the car rental agreement at CV Ilham Motor Jalan Dahlia Gandu Mlarak Ponorogo?, (3) How is the settlement of default in the implementation of car rental? car rental agreement at CV Ilham Motor Jalan Dahlia Gandu Mlarak Ponorogo?, This study aims to (1) find out the incident of default in the car rental agreement that occurred at CV Ilham Motor, (2) find out the forms of default in the car rental agreement that occurred in CV Ilham Motor, (3) to find out the settlement of default problems in implementing the car rental agreement at CV Ilham Motor. In this study, researchers used descriptive analysis and field research, with a qualitative approach.